2021
DOI: 10.3389/fendo.2021.598788
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Melatonin on Neurobehavior and Cognition in a Cerebral Palsy Model of plppr5−/− Mice

Abstract: Cerebral palsy (CP), a group of clinical syndromes caused by non-progressive brain damage in the developing fetus or infant, is one of the most common causes of lifelong physical disability in children in most countries. At present, many researchers believe that perinatal cerebral hypoxic ischemic injury or inflammatory injury are the main causes of cerebral palsy. Previous studies including our works confirmed that melatonin has a protective effect against convulsive brain damage during development and that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…Experimental analysis indicates that wild-type mice having hypoxic-ischaemic brain injury show better performance as compared to PLPPR5-/-mice, irrespective of melatonin treatment. Moreover, melatonin treatment improves behaviour in the tests for wild-type animal models with hypoxic-ischaemic brain injuries, but not for PLPPR5-/-mice [44].…”
Section: Preclinical Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Experimental analysis indicates that wild-type mice having hypoxic-ischaemic brain injury show better performance as compared to PLPPR5-/-mice, irrespective of melatonin treatment. Moreover, melatonin treatment improves behaviour in the tests for wild-type animal models with hypoxic-ischaemic brain injuries, but not for PLPPR5-/-mice [44].…”
Section: Preclinical Studiesmentioning
confidence: 93%
“…Interestingly, studies have shown that perinatal cerebral hypoxic ischaemic injuries as well as inflammatory injuries are the main causes of cerebral palsy. PLPPR5 is an integral membrane molecule of the plasticity-related family of proteins [44]. It is expressed specifically in spinal cord as well as brain and drives the growth of the neurites.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Thirteen studies [ 60 , 62 , 71 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ] report improvement in histological outcomes including reduction in infarct volume, reduction in markers of apoptosis, necrosis, cell death, astrocytosis, and microgliosis. Neurobehavioral studies were also reported in 3 studies [ 62 , 132 , 140 ], observing improved cognitive performance, learning and memory, motor function, and co-ordination. Berger et al (2019) [ 141 ] reported no overall long-term treatment effect based on brain injury volume, diffusion tensor imaging, histology and functional outcomes however the variability of injury in this model was large.…”
Section: Melatonin As a Single Agent For The Low Resource Settingmentioning
confidence: 99%
“…Then, Cas9 and gRNA were injected into fertilized mouse eggs at the same time (see Table 1 for the sequence information for gRNA). The Cas9 protein binds to the target site under the guidance of gRNA, causing DNA double-strand breaks, resulting in the deletion of the base sequence of the target site and ultimately achieving systemic gene knockout (Sun et al, 2021). The strain backgrounds of PRG5 knockout mice and WT wild-type mice are both C57BL/6JNju (see Table 2 for strain information of knockout mice).…”
Section: Animal Preparationmentioning
confidence: 99%
“…To identify whether the PRG5 protein is knocked out in KO mice, we first cut 3-5 mm tail tip tissue from the offspring mice born at the age of 3 days, and used PCR to perform genotype identification, and compare the size of the DNA products of the mice to be identified: Wildtype mice (PRG5 −/− ) = 439 bp, homozygous PRG5 knockout mice (PRG5 −/− ) = 414 bp, heterozygous PRG5 knockout mice (PRG5 ±) = 414 bp + 439 bp. (The process was completed by the Nanjing Institute of Biomedicine, Nanjing University) (Sun et al, 2021).…”
Section: Animal Preparationmentioning
confidence: 99%